A novel antisense lncRNA NT5E promotes progression by modulating the expression of SYNCRIP and predicts a poor prognosis in pancreatic cancer. Issue 18 (8th August 2020) - Zhang, Pengbo; Cao, Meng; Zhang, Yi; Xu, Lei; Meng, Fanchao; Wu, Xinquan; Xia, Tianfang; Chen, Qun; Shi, Guodong; Wu, Pengfei; Chen, Lei; Lu, Zipeng; et al.
Abstract: A novel antisense lncRNA NT5E was identified in a previous microarray that was clearly up‐regulated in pancreatic cancer (PC) tissues. However, its biological function remains unclear. Thus, we aimed to explore its function and clinical significance in PC. The lncNT5E expression was determined in PC specimens and cell lines. In vitro and in vivo studies detected the impact of lncNT5E depletion on PC cell proliferation, migration and invasion. Western blotting investigated the epithelial‐mesenchymal transition (EMT) markers. The interaction between lncNT5E and the promoter region of SYNCRIP was detected by dual‐luciferase reporter assay. The role of lncNT5E in modulating SYNCRIP was investigated in vitro. Our results showed that lncNT5E was significantly up‐regulated in PC tissues and cell lines and associated with poor prognosis. LncNT5E depletion inhibited PC cell proliferation, migration, invasion and EMT in vitro and caused tumorigenesis arrest in vivo. Furthermore, SYNCRIP knockdown had effects similar to those of lncNT5E depletion. A significant positive relationship was observed between lncNT5E and SYNCRIP. Moreover, the dual‐luciferase reporter assays indicated that lncNT5E depletion significantly inhibited SYNCRIP promoter activity. Importantly, the malignant phenotypes of lncNT5E depletion were rescued by overexpressing SYNCRIP. In conclusion, lncNT5E predicts poor prognosis and promotes PC progression by modulating SYNCRIP expression.